Oxygen desaturation and lung ultrasonography as markers of diffuse parenchymal lung diseases severity - Ahmed Sadaka; Asmaa Gomaa; Hoda Abdelgawad; Nashwa H. Abdelwahab; Eman Ahmed Hatata; Hanaa Shafiek (PLoS ONE, 2025)
Purpose we aimed to evaluate lung ultrasound (LUS) and oxygen desaturation as markers for the severity of diffuse parenchymal lung disease (DPLD), specifically the fibrotic subtypes, and correlate the findings with high-resolution computed tomography (HRCT) and other physiologic parameters. Methods A case-control study was conducted recruiting 31 DPLD patients and 20 age-matched healthy controls from our institution. All participants had a spirometry, HRCT, 6-minute walk test (6MWT), echocardiography and full-night cardio-respiratory polygraph. LUS for B-line quantification and pleural examination was performed on 6 zones bilaterally. Results Compared to controls, patients had a statistically significant higher total number of B-lines, lower 6MWT nadir O2 and lower nadir nocturnal oxygen saturation (SpO2). Among patients; fibrotic DPLD (58.1%) had more B-lines, pleural irregularities with or without fragmentation, higher Warrick scores and lower 6MWT nadir SpO2 (p = 0.01, 0.008, < 0.005, 0.03 respectively). There was a statistically significant positive correlation between LUS findings and Warrick score that inversely correlated with the forced vital capacity (FVC)% predicted (p < 0.001). A score of LUS findings, 6MWT nadir SpO2 and time spent with SpO2 < 90% (T90) ≥2 points had a sensitivity of 91.7% and specificity of 66.7% in predicting severe fibrotic DPLD (area under curve (AUC)= 0.832, CI95% = 0.723–0.941, p = 0.001). Conclusions The number of B-lines and pleural irregularities in LUS, nocturnal desaturation and exercise desaturation can play a role as markers of DPLD severity.